APLIKASI TEKNOLOGI PENGOLAHAN AIR SEDERHANA UNTUK MASYARAKAT PEDESAAN - Herlambang, Arie; Said, Nusa Idaman (Jurnal Air Indonesia, 2005)
The level of water services by PDAM (Local Water Service Company) is still 19,4% of Indonesian population. Most of them still rely on groundwater, spring, river and rain. In the big and medium cities the level of water services higher between 40 Ã¢â‚¬â€œ 50 and 20 - 30% respectively, but in rural still very low. Recently many source of water is contaminated by domestic, industry, and agricultur waste due to lack of attention of water users to environment.Ã‚Â  Beside, some dense populated areas with low sanitation fasility make many shalow well contaminated by E.coli. For improving rural water services, It needsÃ‚Â  government policy that encourage bigger role of rural comunity to develop their ability and organization that maintain and protect source, process, production and distribution of water. Information ofÃ‚Â  Simple Water Treatment Technology is an important that must be distributed to people who live in village or remote areas,Ã‚Â  in order to improve their knowledge. BPPT has been along time to develop many kind of water treatment technologies for treating river water, groundwater, peatwater, calcareous water,poluted water,Ã‚Â  brachist water or even sea water to make clean water or potable water. Many of those technologies have already applied in many areas in Indonesia, and up to now BPPT still develop many kind of water treatment technologies for the future.Ã‚Â Kata Kunci : air bersih, pengolahan air, masyarakat pedesaan.Ã‚Â